Information Technologies for Supporting Administrative Activities of Large Organisations - Al-Azzeh, Jamil (DESIDOC Journal of Library & Information Technology, 2018)
Study describes a specified analytical method and model for the organisational management of a company. The proposed solutions allow for revealing information resources, which can be used to support management decisions adoption and control of plans. Information obtained from programs and information systems of the electronic document flow of organisations were used as data sources. The result of configuration investigation and characteristics of information exchange in information systems can be used as administrative decisions support in the organisation. The conducted research allows for improved approaches to the creation and modernisation of effective information systems of universities. The offered software of administrative activity support allows us to increase the flexibility and adaptability of existing information systems and electronic document flow (program complexes) to increase the efficiency of their operations.